Improving Student Learning Outcomes Through the Scientific Approach Method in the Hadith Studies Subject for Grade XI Religious Class at MA Unggulan K.H. Abd. Wahab Hasbulloh Tambak Beras Jombang - Purbaningrum, Ajeng; Prihatiningtyas, Suci; Husna, Asiyah Lu'Lu'ul; Darmawan, Faridl (APPLICATION: Applied science in Learning Research, 2024)
The science of hadith plays a crucial role in Islamic education, aiding in the interpretation and clarification of Quranic teachings. This study investigates the impact of implementing a scientific approach in teaching Hadith Science at MA Unggulan K.H. Abd. Wahab Hasbulloh. Using a pre-experimental design with 34 students, pretest and posttest scores were analyzed to assess learning outcomes. Results indicate significant improvement post-implementation, with most students achieving "Very Good" and "Good" grades. The average N-Gain score of 0.6 suggests moderate improvement, affirming the effectiveness of the scientific approach in enhancing student understanding and engagement. This study contributes to the discourse on effective pedagogical methods in religious education, emphasizing active learning and critical thinking skills development.